Morphological, mechanical, and biological evolution of pure hydroxyapatite and its composites with titanium carbide for biomedical applications. Issue 13 (1st July 2022) - Avinashi, Sarvesh Kumar; Singh, Piyush; Shweta; Sharma, Kriti; Hussain, Ajaz; Singh, Divya; Gautam, Chandkiram
Abstract: Pure hydroxyapatite (HAp) was synthesized successfully via a wet chemical precipitation method. To study the influence of TiC (weight % of 5, 10, 15) substitution on the mechanical behavior of pure HAp, its composites with TiC were synthesized using a solid-state reaction method. Herein, detailed investigations of pure HAp and its composites using X-ray powder diffraction (XRD), FTIR spectroscopy, Raman spectroscopy, UV-VIS spectroscopy, SEM followed by EDAX and particle size analysis were carried out. XRD study reveals the phase stability of the prepared HAp and composite samples. However, FTIR and Raman spectroscopic studies revealed the bond formation among the various constituents. Mechanical behavior of HAp, and its composites with TiC were studied using numerous parameters like density, Young's modulus, fracture toughness, and load absorption capability. Based on these studies, it was revealed that the addition of 5 wt % substitution of TiC sintered at 1200 °C significantly enhanced the mechanical properties of pure HAp. Hence, 5 wt % of TiC composite 95HAp-5TiC showed the best mechanical characteristics such as density (2.3060 g/cm 3 ), Young's modulus (14.53 MPa), fracture toughness (19.82 MPa m 1/2 ), maximum compressive strength (186 MPa) respectively. Cytotoxicity and osteogenic activities of the synthesized pure HAp and its composite, 95HAp-5TiC were performed using osteoblast cells (mouse calvarial) at different concentrations of the samples (0.01 μg, - 100 μg). From the above studies, the cell viability and ALP activities of the composite, 95HAp-5TiC found to be excellent than that of pure HAp. Hence, this composite sample may be utilized for bone implant applications.